1998
DOI: 10.1002/(sici)1099-0984(1998090)12:5<345::aid-per332>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental sources of consistency and variability in positive and negative mood

Abstract: Several studies have found a genetic in¯uence on person  situation interactions of behaviours and emotions. For ®ve situations we assessed current positive and negative mood for a sample of 168 monozygotic and 132 dizygotic adult twin pairs completing self-report rating scales. We used structural equation model ®tting to estimate genetic and environmental in¯uences on the stability and variability of moods across situations. Our results indicate that genetic as well as shared and nonshared environmental in¯u-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 26 publications
0
25
1
Order By: Relevance
“…Consistent with this hypothesis, a study of 105 twin pairs (18–72 years old) found moderate genetic influences on negative affect (.34) but not on positive affect (.00) when differences in affect were assessed as traits at one time point (Baker, Cesa, Gatz, & Mellins, 1992). Another study, with 300 pairs of 18- to 70-year-old twins, found similar results for genetic influences on negative and positive affect assessed as traits at one time point (.24 vs. .18; Riemann, Angleitner, Borkenau, & Eid, 1998). Also, in a study of 260 pairs of 18- to 46-year-old female twins, genetic influences on the average of positive affect assessed over 5 consecutive days were nonsignificant (.19; Menne-Lothmann et al, 2012).…”
mentioning
confidence: 66%
“…Consistent with this hypothesis, a study of 105 twin pairs (18–72 years old) found moderate genetic influences on negative affect (.34) but not on positive affect (.00) when differences in affect were assessed as traits at one time point (Baker, Cesa, Gatz, & Mellins, 1992). Another study, with 300 pairs of 18- to 70-year-old twins, found similar results for genetic influences on negative and positive affect assessed as traits at one time point (.24 vs. .18; Riemann, Angleitner, Borkenau, & Eid, 1998). Also, in a study of 260 pairs of 18- to 46-year-old female twins, genetic influences on the average of positive affect assessed over 5 consecutive days were nonsignificant (.19; Menne-Lothmann et al, 2012).…”
mentioning
confidence: 66%
“…Surprisingly, self-ratings of conscientiousness by individuals living in societies with poor economic development (for example, several countries in Africa) were higher than the self-ratings for conscientiousness among individuals living in the economically most developed societies (e.g., Japan; Allik & McRae, 2004). The heritability values for the Big Five dimensions generally hover around 0.5 across samples (Lensvelt-Mulders & Hettema, 2001;Riemann, Angleitner, Borkenau, & Eid, 1998). However, when individuals are filmed in a variety of situations and when judges rate each person's film records for traits related to the Big Five, the resulting heritability values are much lower (0.12) and most of the variance is unshared (Borkenau, Riemann, Rainer, Spinath, & Angleitner, in press).…”
Section: The Special Properties Of Wordsmentioning
confidence: 99%
“…First, certain traits might be modifiable risk factors for poor PCC during medical training. Evidence on the partial genetic basis (17) and moderate stability (18) of personality have led to the misperception that personality is totally immutable, challenged by recent meta-analyses indicating that change is possible over the adult life course and particularly so prior to age 30, when early medical training is completed (19, 20). Indeed, medical training itself may influence dispositional outlook and behavior--empathy may decline (21) and cynicism increase (22), suggesting potential unintended consequences on communication style.…”
Section: Introductionmentioning
confidence: 99%